BUDIDAYA JAMUR TIRAM (PLEURETUS.sp)SEBAGAI ALTERNATIF USAHA BAGI MASYARAKATKORBAN ERUPSI MERAPI DI DUSUN PANDAN, WUKIRSARI,CANGKRINGAN, SLEMAN DIY - Drajat Pramiadi, Victoria Henuhili, Siti Umniyatie, Astuti, (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2013)
This activity aims to provide experience in white oyster  mushroomcultivation and to offer alternative business opportunity for recovering localeconomy through white oyster mushroom cultivation in the hamlet ofPandan, Wukirsari, Cangkringan, Sleman, DIY.Practice, mentoring, and discussion form the main methods in thisactivity that consist of constructing mushroom house, preparing the growingmedia, sterilization method, mushroom inoculation, and maintenancemethod during incubation.This activity provides practical experience in white oyster mushroom(Pleuretus.sp) cultivation for local community in the hamlet of Pandan,Wukirsari, Cangkringan, Sleman, DIY. Within 37 days of incubation, 168kilograms of wet white oyster mushroom has been harvested and manymore in the next three months. The profit gained in 4 months is around Rp790.000,-, therefore this activity could be an alternative businessopportunity for the local community. Factors that need to be taken intoaccount during incubation are room temperature (26áµ’C), lighting, humidityof media (60%), room humidity (80-90%), and disease and pests control.